Collision-induced dissociation at TRIUMF's ion trap for atomic and nuclear science - Jacobs, Andrew; Andreoiu, C.; Bergmann, J.; Brunner, T.; Dickel, T.; Dillmann, I.; Dunling, E.; Flowerdew, J.; Graham, L.; Gwinner, G.; Hockenbery, Z.; Kootte, B.; et al. (International journal of mass spectrometry, 2022)
The performance of high-precision mass spectrometry of radioactive isotopes can often be hindered by large amounts of contamination, including molecular species, stemming from the production of the radioactive beam. In this paper, we report on the development of Collision-Induced Dissociation (CID) as a means of background reduction for experiments at TRIUMF's Ion Trap for Atomic and Nuclear science (TITAN). This study was conducted to characterize the quality and purity of radioactive ion beams and the reduction of molecular contaminants to allow for mass measurements of radioactive isotopes to be done further from nuclear stability. This is the first demonstration of CID at an ISOL-type radioactive ion beam facility, and it is shown that molecular contamination can be reduced up to an order of magnitude.
Available online 24 September 2022, version of record 5 October 2022
Gesehen am 25.01.2023